Impacts of climate change on diarrhoeal disease hospitalisations: How does the global warming targets of 1.5–2°C affect Dhaka, Bangladesh? - Haque, Farhana; Lampe, Fiona C.; Hajat, Shakoor; Stavrianaki, Katerina; Hasan, S. M. Tafsir; Faruque, A. S. G.; Ahmed, Tahmeed; Jubayer, Shamim; Kelman, Ilan (PLOS Neglected Tropical Diseases, 2024)
Author summary Dhaka, a resource-constrained, crowded city in Southeast Asia, struggles with serious public health issues, especially a high number of diarrhoeal diseases. Climate change is worsening Dhaka’s environmental problems by making Dhaka hotter and deteriorating water quality. While some studies have already looked at how weather affects diarrhoea in Bangladesh, few have examined the future impact of climate change. This study explored how rising temperatures might affect diarrhoea in Dhaka in the future. Using advanced statistical methods, the researchers analysed information from nearly 3 million diarrhoea patients treated at a major hospital in Dhaka from 1981 to 2010. The study found that higher daily temperatures significantly increased the risk of diarrhoea for all age groups, even after considering other factors like heavy rain, humidity, and seasonal patterns. Based on future temperature predictions, even if global warming is limited to 1.5 to 2°C, as targeted by international agreements, diarrhoea cases could rise by 4.5% to 7.4% by the end of the century. The increase could be even higher for children under 5 years old, with hospital admissions going up by 5.7% to 9.4%. This highlights the need for Dhaka city to better prepare for managing and preventing diarrhoeal diseases in the future.